Etude des propriétés thermomécaniques et du phénomène de fissuration périodique des films d’oxyde à haute température: Cas du système Ni (111)/NiO (001) - Vallino, Nicolas; Lahoche, Laurent; Roelandt, Jean-Marc; Lorman, Vladimir; Rochal, Sergei (European Journal of Computational Mechanics, 2003)
We present a model for the calculation of stress and strain fields in the nickel oxide film during an oxidation process. It is based on a cristallographic and thermodynamic analysis of the interface. A numerical approach permitted to validate our model. The comparison of the experimental data obtained by performing a dissymmetrical oxidation with the numerical results is in good agreement. The model has also been used to define the initial states of a 2D or 3D numerical model which compute the behavior of the coated cracked metallic/oxide structure in the presence of cracks under mechanical load.